THE IMPACT OF HUMAN RESOURCE MANAGEMENT PRACTICES ON ACHIEVING THE COMPETITIVE ADVANTAGE OF ORGANIZATIONS (World Economics and Finance Bulletin, 2022)
Human resources are the important component to reach the desired goals and objectives. Its importance lies in its influential role in raising the efficiency of the organization's management and the performance of its tasks and activities as a final result of the efficiency and effectiveness of its internal and external activities. A financial challenge for the organizations and the clients they serve, but, arguably more importantly, for most of them the time spent on a job far exceeds the time spent away from work. Talent It seeks to ensure that the roles that individuals play in the client's face with interpersonal skills
Keywords: human resources; competitive advantage; institutions